Geologia da porção extremo norte do Bloco Guanhães, Orógeno Araçuaí (Minas Gerais) - Úrsula Roxanne Leandro (2021)
The Guanhães Block is one of the most important basement inliers within the Araçuaí-West Congo Orogen. This orogenic segment was built on the eastern margin of the São Francisco Craton in the Neoproterozoic-Cambrian boundary. The Guanhães Block is composed by Archean TTG complexes and Archean to Cryogenic metavolcanosedimentary sequences, as well as Paleo to Neoproterozoic igneous and Paleoproterozoic sedimentary units. New field, petrographic, geochemical and geochronological (U-Pb; LA-ICP-MS) data are presented for the Guanhães Complex, the Capelinha Formation (Macaúbas Group) and associated units. For the first time are presented geochronological data from detrital zircon grains for the Serra Negra Formation, in the northwestern Guanhães Block. The gneiss of the Pedra Menina region integrate the Guanhães Complex, whose protholith crystallization ages are defined by two U-Pb discordias with upper intercepts at 2.86 and 2.7 Ga and lower intercepts at 521 and 607 Ma (interpreted as metamorphic ages). These basement gneisses present granitic to granodioritic compositions and magnesian, peraluminous affinity and plot as subalkaline magmatic series. The samples from the Guanhães Complex are enriched in LILE, Th and U, and present negative anomalies of Nb, P and Ti. All the samples are enriched in LREE in relation to HREE and correspond to metaigneous rock with Archean TTG affinity. The Serra Negra Formation is a sedimentary succession with maximum depositional age at 1.9 Ga (quartzite) that includes a narrow basal layer of schists and metaconglomerates, followed by extensive saccharoidal quartzites, which seems to be formed in coastal sedimentary environments. The Capelinha Formation includes quartzites, schists and expressive marbles lenses. The data obtained demonstrates that this unit has a wider territorial extension towards the south than postulated in their original definition. It was obtained a Stenian (1.16 Ga) maximum depositional age for schist from the Capelinha Formation. Chemical analyzes for the amphibolite bodies suggest affinity with continental intraplate tholeiitic basalt as protoliths of these rocks. The REE patterns, normalized to chondrite, show enrichment in the LREE (La/Yb = 2.4 to 8.21), and relatively low contents of HREE. These results integrated with mapping and geological associations suggest a correlation with metamafic rocks of Capelinha Formation type-area and with the magmatic record of the Tonian rifting event, with possible correspondent in the African counterpart in the context of the São Francisco-Congo paleocontinent. The Ediacaran leucogranite that intrude the base of the Serra Negra Formation present a crystallization age at 566 Ma and is interpreted as a register of the collisional magmatism of the Araçuaí-West Congo Orogen. Two hypotheses were suggested for tectonic significance of the Serra Negra Formation: i) the deposition in a syn-orogenic basin at the end of the Paleoproterozoic Minas-Bahia orogeny or ii) the deposition in the Tonian rift basin, together with the Capelinha Formation (ca. 957 Ma).